Levels of microbial diversity affect the stability and function of dark fermentation bioreactors - Navarro-Díaz, Marcelo; Aparicio-Trejo, Valeria; Valdez-Vazquez, Idania; Carrillo-Reyes, Julián; Avitia, Morena; Escalante, Ana E. (Frontiers in Industrial Microbiology, 2024)
Climate change and pollution drive the need for fossil fuel alternatives. Dark fermentation offers promise through the use of microbial consortia to convert organic matter into hydrogen gas. Persisting challenges like instability and low yields may stem from reduced diversity of the anaerobic digestion communities that serve as inoculum and undergo aggressive pretreatments and culturing conditions. This study explores the impact of diversity loss on function, focusing on biogas production and stability. Two treatments, with and without aggressive pretreatment, were tested on 12 replicate bioreactors each, resulting in differing microbial diversity levels. Microbial communities were assessed via 16S amplicon sequencing, monitoring biogas production, volatile fatty acids, and testing invasion susceptibility. The two treatments exhibited divergent assembly and functional trajectories, although replicates within each treatment ultimately converged into similar compositions and stable levels of biogas production. Heat-treated bioreactors showed a 91.5% biogas increase but exhibited higher invasion susceptibility compared to non-treated. Non-treated bioreactors showed unique species associations with biogas production (e.g. Ethanoligenens harbinense and Enterococcus olivae), distinct from the commonly studied Clostridium group. These findings provide insights into the effects of diversity loss on stability, elucidating differences across taxonomic and functional stability as well as invasion susceptibility. Moreover, the identification of novel bacterial groups associated with hydrogen production suggests promising directions for future research to enhance microbial consortia control and design in dark fermentation.